2010
DOI: 10.4061/2010/978520
|View full text |Cite
|
Sign up to set email alerts
|

Fertility Rates of Ewes Treated with Medroxyprogesterone and Injected with Equine Chorionic Gonadotropin plus Human Chorionic Gonadotropin in Anoestrous Season

Abstract: The aim of the present paper was to investigate the efficiency of the equine chorionic gonadotropin (eCG) plus human chorionic gonadotropin (hCG) associated with medroxyprogesterone acetate (MAP) to estrous ewes synchronization. Ninety Texel ewes were investigated during seasonal anoestrous. The ewes received intravaginal sponges containing MAP (60 mg) for nine days. At the time of sponges' withdrawal, the ewes were divided into three groups (G): (1) receiving 2 mL of saline i.m. (n = 30), (2) receiving eCG 40… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 16 publications
2
7
0
1
Order By: Relevance
“…The lambing rate in the differently treated ewes was 61.5, 88.5 and 92.3%, respectively. The results of the present study are compatible with the study results of Santos et al (2010) who demonstrated that short-term progestagen treatment does not improve the fertility of ewes, as was previously reported (Husein et al, 2007;Ustuner et al, 2007;Amer and Hazzaa, 2009). In the present study, the multiple birth rate and litter size in the treatment groups were lower than the values observed in hormone treated native ewes of Turkey (Askin, 1988;Koyuncu and Yerlikaya, 2007;Karaca et al, 2009).…”
Section: Resultssupporting
confidence: 94%
“…The lambing rate in the differently treated ewes was 61.5, 88.5 and 92.3%, respectively. The results of the present study are compatible with the study results of Santos et al (2010) who demonstrated that short-term progestagen treatment does not improve the fertility of ewes, as was previously reported (Husein et al, 2007;Ustuner et al, 2007;Amer and Hazzaa, 2009). In the present study, the multiple birth rate and litter size in the treatment groups were lower than the values observed in hormone treated native ewes of Turkey (Askin, 1988;Koyuncu and Yerlikaya, 2007;Karaca et al, 2009).…”
Section: Resultssupporting
confidence: 94%
“…This indicated that FIS/eCG (400 IU) was an optimum scheme for estrus synchronization in Lanzhou fattailed ewes. The findings were highly consistent with early reports of Santos et al (2010) and Bianor et al (2012). The results of Santos et al (2010) indicated that the pregnancy and lambing rates were 86% vs. 56%, and 120% vs. 56% in ewes intramuscularly injected with eCG 400 IU and eCG 400 IU plus hCG 200 IU at the time of intravaginal sponges.…”
Section: Discussionsupporting
confidence: 93%
“…Hackett et al (1981) reported that 83% ewes (24/29) had viable foetuses after 15 mg PGF2α and 500 IU eCG treatments. Santos et al (2010) reported that the ewes were injected intramuscularly with eCG 400 IU and eCG 400 IU plus hCG 200 IU at the time of intravaginal sponge (containing 60 mg medroxyprogesterone acetate, MAP) withdrawal. The estrus rates of both treatments were 90% and 86%.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Se introdujo un hilo de algodón para extraerlas (Fukui et al 1987;Espinoza et al 2003). Las esponjas se desinfectaron con etanol al 90%; se dejaron secar en cámara de flujo laminar; luego se impregnó la superficie con 60 mg de MAP (Laboratorios Afford, obtenidos de Laboratorios Calox, Costa Rica) (Fukui et al 1999;Zarwaki 2001;Ungerfeld et al 2003;Barrett et al 2004;Catalano et al 2005;Catalano et al 2007;Santos et al 2010); diluidos en 1 mL de etanol al 90%; dispersando el fármaco, en forma lineal, sobre la superficie (Robinson et al 1968). Posteriormente, se secaron, en una cámara de flujo laminar con protección de la luz solar.…”
Section: Preparación De Las Esponjasunclassified